Analysis of the Effect of CSR on Corporate Value Mediated with Profit Management - Ivone Ivone; Alvina Alvina (Universitas Kristen Maranatha, 2023)
With the help of control variables such as return on asset, leverage, book to market value, and firm size, this research seeks to determine how effective earning management can be as an intervening variable in a relationship between corporate social responsibility and firm value. This study uses secondary data of companies listed on the IDX (Indonesia Stock Exchange) with data collected from 2018 to 2022 as a sample in the data analysis method. The data collection technique with a sample of 36 companies over a five-years so that the total sample is 180. The results of the study showed that the corporate social responsibility variable has a significant negative effect on firm value, corporate socialresponsibility has no significant effect on earnings management, and earnings management has a significant negative effect on firm value, and earnings management cannot mediate the relationship between Corporate Social Responsibility and firm value. Keywords: Firm Value, Earning Management, and Corporate Social Responsibility